Pengaruh Perceived Value, Customer Satisfaction dan Trust terhadap Customer Loyalty Restoran XYZ di Tangerang - Innocentius Bernarto (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2017)
The objectives of this study are to know: 1) Is perceived value has a positive influence towards customer loyalty, 2) Is perceived value has a positive influence towards customer satisfaction, 3) Is customer satisfaction has a positive influence towards customer loyalty, 4) Is customer satisfaction has a positive influence towards trust, and 5) Is trust has a positive influence towards customer loyalty. This study took 100 Management students from ABC university who have ever visited XYZ Restaurant in Tangerang as respondents. This study is using PLS-SEM (Partial Least Square – Structural Equation Modeling) to do data processing. The finding of this study showed that perceived value has a positive influence towards customer satisfaction and customer loyalty. This study also showed that customer satisfaction has a positive influence towards customer loyalty and trust. However, from this study, it was found that trust has no positive influence towards customer loyalty. This study can be used as input for the management of XYZ restaurant to give better service to the customers so that they do not only trust the restaurant but also has loyalty to it. Keywords: perceived value, customer satisfaction, trust, customer loyalty